50 first dates [videorecording (DVD)] - Segal, Peter, 1962-; Giarraputo, Jack; Golin, Steve; Juvonen, Nancy; Wing, George; Sandler, Adam; Barrymore, Drew; Schneider, Rob, 1963-; Astin, Sean; Strus, Lusia; Clark, Blake, 1946-; Aykroyd, Dan; et al. (Columbia TriStar Home Entertainment : Sony Pictures Home Entertainment, 2004)
Henry Roth lives an enviable life in a Hawaiian paradise, spending every night with a different beautiful tourist in search of an island fling. It's a great life, no strings attached ... until he meets Lucy. He and Lucy hit it off right from the start, but the next day she acts like she doesn't know him. Lucy suffers from short-term memory loss, so every night all memory of her day is erased. But a man in love will go to great lengths to win the girl of his dreams. In an effort to help her remember him, he makes a video tape for her to watch every morning.